If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 12 = 2y Reorder the terms: 12 + 3y = 2y Solving 12 + 3y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 12 + 3y + -2y = 2y + -2y Combine like terms: 3y + -2y = 1y 12 + 1y = 2y + -2y Combine like terms: 2y + -2y = 0 12 + 1y = 0 Add '-12' to each side of the equation. 12 + -12 + 1y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 1y = 0 + -12 1y = 0 + -12 Combine like terms: 0 + -12 = -12 1y = -12 Divide each side by '1'. y = -12 Simplifying y = -12
| 2x^2-8x+2y^2+20y=12 | | 3s+9=2(s-6) | | 3x-8+2x+17= | | 5x+3x+12=28 | | 3x+5(2)=10 | | 3(7+3x)=3(x-3) | | 2x^2-8x+2y^2+20y+12=0 | | 24(2x-1)=8(x+2)+2x | | -2u+16=-8u-8 | | 2(b+1)-(4+b)=-7 | | 16x-4=2(7x-6)+2x+8 | | 3y-4x=20 | | 111=13x+6 | | 10-4x+11x=-8x+4x | | 4t+7-t=18 | | 2y+7=2y+7 | | .75w-.5w-4=12 | | 11b-9b+5=17 | | y^2+2xy+2x-5=0 | | g=ar | | 1.75w-.5w-4=12 | | -2-3x=3+ | | -7y+6=-8y+4 | | 2x+3y-20=-15 | | -56+42x=6x+6 | | 8[5x+7(3+4x)]-16x-8= | | 3-5q=9-4q | | 0.01x-0.1=-x+10 | | 3x+5x+20= | | 5d+2(2d-3)-(-2)= | | 63x^2+72x^2= | | 4(2x-6)=18 |